Correction of Recurrent Equinus Deformity in Surgically Treated Clubfeet by Anterior Distal Tibial Hemiepiphysiodesis. Issue 9 (October 2020) - Ebert, Nicola; Ballhause, Tobias M.; Babin, Kornelia; Schelling, Katrin; Stiel, Norbert; Stuecker, Ralf; Spiro, Alexander S.
Abstract : Background: Residual or recurrent equinus deformity is a common problem in surgically treated clubfeet. This deformity may occur due to soft tissue–related reasons or due to bony deformity. An increased anterior distal tibial angle (ADTA) was previously found in 48% of the operated clubfeet. This study aimed to determine the efficacy and safety of anterior distal tibial hemiepiphysiodesis (ADTE) in the treatment of recurrent equinus deformity in patients with an increased ADTA. Methods: Eighteen children (23 feet) treated by ADTE to correct recurrent equinus deformity in surgically treated clubfeet were included in this retrospective, single-center study. ADTE using 8 plates was performed in children with an increased ADTA (>82 degrees) and inability to dorsiflex the ankle (⩽0 degree of dorsiflexion). The mean patient age was 11.3 years (range: 10.2 to 12.9 y). All patients had completed treatment with implant removal after an average of 20.3 months (range: 9 to 37 mo). Results: The mean preoperative ankle dorsiflexion significantly improved from −3.3 degrees (range: −20 to –0 degrees) to 6.1 degrees (range: −15 to 10 degrees) at the time of 8-plate removal (correction rate: 9.4 degrees; P <0.0001). The ADTA was a mean of 87.5 degrees (range: 83 to 110 degrees) before surgery and significantly improved to 75.8 degrees (range: 63 to 106 degrees) at the time of implant removal (correction rate: 11.7 degrees; P <0.0001). Average follow-up was 43.9 months (range: 10 to 76 mo). Follow-up examinations were continued in 11 patients (13 feet) after implant removal. Changes of ankle dorsiflexion (mean: −2.5 degrees) and ADTA (mean: 3.6 degrees) occurred in this group. Conclusions: ADTE was safe and effective in the treatment of recurrent equinus deformity in surgically treated clubfeet with increased ADTA. Deterioration of ankle dorsiflexion and ADTA occurred after implant removal in some cases. The results of this study have to be analyzed with caution due to the limited number of included patients and its retrospective nature. Level of Evidence: Level IV—retrospective case series.